Writing the Self-at-War: World War I Popular Writings as “Technologies of the Self” - Mazzini, Federico (Open Science Journal, 2017)
Based on the analysis of more than 150 diaries and memoirs, this article highlights the rhetorical strategies used to define the self and shape the idea of war that characterized a specific peasant community, the Italian-speaking soldiers from the Trentino region that fought for Austria-Hungary in World War I. Through this case study the essay discusses how the Foucauldian notion of “technology of the self” can be applied to the study of war testimonies and to the historiographical debate on the nature of World War I “war culture”. By looking at the texts not in their message but in their form and in their function for the authors the study proposes a methodology to interpret sources that have been often deemed too repetitive and hermetic to be part of a systematic historical analysis.